Anthelmintic resistance in goat herds-In vivo versus in vitro detection methods - Babják, M; Königová, A; Urda Dolinská, M; Vadlejch, J; Várady, M (Veterinary parasitology, 2018)
Anthelmintic resistance (AR) is a serious threat to animal health and has a major economic impact worldwide due to production and financial losses. The aim of this study was to determine the occurrence of AR on 30 goat farms in Slovakia during the pasturing seasons and to compare three widely used in vitro and in vivo methods for detecting AR in field conditions. A three-year survey was conducted during the pasturing seasons of 2014-2016. Goats on each farm were split into treated and control groups and were treated by recommended (5 mg/kg body weight) and double doses (10 mg/kg b.w.) of albendazole. Comparisons between percent reduction in a faecal egg count reduction test (FECRT) and an egg hatch test (EHT) and the presence of L3 larvae in a larval development test (LDT) using resistant concentrations of benzimidazole (BZ) were monitored after treatment. The FECRT indicated percent reductions of 69.2-86.2% for the single dose and of 36.3-45.4% for the double dose. The EHT indicated that all farms had BZ-resistant nematodes. Low (<15% hatching) and high (>15% hatching) levels of resistance were detected on 13 and 17 farms, respectively. The LDT failed to detect resistant larvae on seven farms but detected low and high levels of resistance on seven and 14 farms, respectively. The data indicate a moderate correlation between in vitro and in vivo tests for detecting BZ resistance among the 30 goat farms. The hatching detected by the EHT and the presence of L3 larvae by the LDT at resistant BZ concentrations provided reasonable identification of low levels of resistance in the parasite populations, but the use of a double dose for a treatment may underestimate the real occurrence of low levels of resistant parasites on goat farms.
Keywords: kozy; Drug Resistance; Ostertagia; Slovakia; Slovenská republika; Trichostrongylus; benzimidazoly; Goats; techniky in vitro; vztah mezi dávkou a účinkem léčiva; Benzimidazoles; léková rezistence; Anthelmintics; larva; Animals; anthelmintika; zvířata; Larva; Haemonchus; Dose-Response Relationship, Drug; In Vitro Techniques